PERENCANAAN SISTEM PENDUKUNG PENGAMBILAN KEPUTUSAN PENERIMAAN TARUNA DENGAN METODE PROMETHEE (STUDI KASUS SELEKSI TARUNA AKMIL) - Harry Budiharjo; Herry Sofyan; Suparja Suparja (Jurusan Teknik Informatika, 2015)
Admissions cadets have an important role in preparing human resources to be formed into officers candidates in Indonesian armed forces. There are several requirements personality, good academic marks and strong physical. In cadets admissions, there are some test must be passed such as mental of ideology and interview, administration, psychology, academic helth, and physic. Those criteria is a must to filled in order to obtain the right candidates. Implementation of selection need a right system and good method in order to get a right choice. Promethee method is one of order or priority determination in the multi criteria analysis. It is very precise because allegations of dominance criteria use the value in the outranking relationship, so that obtain several alternative solution to make decision. From the calculations result is obtained that the determination of the rank by promethee gives better result compared on method during this time. Promethee method combines quantitative and qualitative , whereas used method during this time only use quantitative method where only depend on value multiplied by the weight of importance